Familial mutation in Caffey disease with reduced penetrance: A case report - Özdemir, Özmert M. A.; Tancer-Elçi, Hazal; Polat, Aziz; Güçtürk, İnci; Tepeli, Emre; Zeybek, Selcan; Ayaz, Akif (The Turkish Journal of Pediatrics, 2016)
Caffey disease is a rare condition of early infancy, characterized by soft tissue swelling, bone lesions, and hyperirritability. Its typical radiological finding is periosteal new bone formation. It can be sporadic or inherited in an autosomal dominant manner. There is no specific treatment. In symptomatic cases, non-steroidal anti-inflammatory drugs such as ibuprofen, indomethacin, or naproxen can be used. This is a report of an infant who presented with restlessness, irritability, and swelling over his shins, diagnosed as Caffey disease. Although there was no family history, the genetic analysis revealed heterozygous missense mutation (c.3040C > T) in type-I-collagen-alpha-1-chain gene in the patient in addition to his mother, grandmother, aunt, and cousin. After indomethacin therapy, the complaints of the patient were completely resolved and his bone lesions were significantly improved. This case report is a familial form of Caffey disease from Turkey, with proven heterozygous mutation in the patient and the family members.
Keywords: COL1A1; Caffey disease; infant; mutation